Upaya Meningkatkan Prestasi Belajar IPA Pada Materi Sifat Sifat Benda Melalui Penerapan Metode Pembelajaran Demonstrasi Pada Siswa Kelas III SDN 013 Tambusai Utara Tahun Ajaran 2013/2014 - Barma Juita (STKIP Rokania Pasir Pangaraian, 2018)
IPA is a subject studied by students of Class III SD. One of the science materials that is difficult to understand students in Class III SD is the Nature of Nature. The low understanding of the students on the properties caused by the students have difficulty in understanding the material presented by the teacher. Teachers speak more, so students are not actively involved in learning and it is difficult to get a deep understanding. This affects the low learning outcomes of students on the material properties. The essence of IPA is the IPA as a product, attitude, and process. With IPA science teaching is not only giving priority to the concept of IPA concept, but it needs to involve the five senses of students maximally. One effort that can be done to overcome the low achievement of third grade students of SD on the material properties by maximizing the five senses of students is the method of demonstration. The problem in this research is